PENINGKATAN KETERAMPILAN LITERASI SASTRA MELALUI STRATEGI SAMBEL TUKAR PADA KELAS IV MI MISBAHUSSUDUR - Idamatussilmi, Idamatussilmi; Gandi Wijanarko, Andrian (JISPE Journal of Islamic Primary Education, 2022)
This study aims to find out the improvement of literary literacy skills through sambel tukar (one work learning) strategy on the theme of my goals in grade 4 mi Misbakhussudur Malangsari. This type of research is class action research (PTK) or Classroom Action Research using research models from Kemmis and Tanggrat namely planning, action, observation, reflection. The study was conducted in 2 cycles with subjects of 18 students consisting of 8 men and 10 women. Data analysis used by researchers is data analysis with descriptive techniques developed by Miles and Huberman. The results of this study show that literary skills through the Sambel Tukar strategy have improved both individually and classically. The increase is seen from the percentage in cycle I of 53.4% increased in cycle II to 72.6%.